System governance towards improved patient safety Key functions, approaches and pathways to implementation - Auraaen, Ane (OECD Publishing, 2020)
Safety governance refers to the approaches taken to minimise the risk for patient harm across an entity or system. It typically comprises steering and rule-making functions such as policies, regulations and standards. To date, governance has focused on the clinical level and the hospital setting, with limited oversight and control over safety in other parts of the health system. All 25 countries that responded to a 2019 OECD Survey of Patient Safety Governance have enacted legislation that aims to promote patient safety. These practices include external accreditation and inspections of safety processes and outcomes. Safety governance models are also moving away from punishment and shaming towards increased trust and openness. Learning from success as well as failures represents a paradigm shift in safety governance, an approach that has been increasingly adopted in OECD countries
Keywords: Social Issues/Migration/Health